2019
DOI: 10.1111/jgh.14686
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir alafenamide for hepatitis B virus infection including switching therapy from tenofovir disoproxil fumarate

Abstract: Background and Aim: Tenofovir alafenamide (TAF) is a new prodrug of tenofovir, enabling treatment of patients with hepatitis B virus (HBV) infection at a lower dose than tenofovir disoproxil fumarate (TDF), via more efficient delivery of tenofovir to the hepatocytes. We compared the efficacy and safety of TDF and TAF and investigated switching from TDF to TAF therapy. Methods: Consent for TDF and TAF therapy was obtained from 117 and 67 patients from August 2014 to January 2018. In total, 45 and 14 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
71
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 34 publications
(41 reference statements)
13
71
2
1
Order By: Relevance
“…Furthermore, since complete eradication of HBV is exceedingly difficult with current treatments, continuous treatment is required. Based on previous reports and the present study, which found an improvement in a short period of time, switching to TAF in patients with renal and tubular dysfunction appears to be effective regardless of previous NA administration duration ( 43 , 44 ). Therefore, switching to TAF should be considered, even in patients treated with NAs who have not experienced side effects.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, since complete eradication of HBV is exceedingly difficult with current treatments, continuous treatment is required. Based on previous reports and the present study, which found an improvement in a short period of time, switching to TAF in patients with renal and tubular dysfunction appears to be effective regardless of previous NA administration duration ( 43 , 44 ). Therefore, switching to TAF should be considered, even in patients treated with NAs who have not experienced side effects.…”
Section: Discussionsupporting
confidence: 74%
“…A real-world study also reported that switching from TDF to TAF significantly reduced tubular dysfunction markers, including the U-BMG/Cr and retinol-binding protein-creatinine ratio in 3 months ( 43 ). A previous study also reported that not only tubular dysfunction markers, but also eGFR, significantly improved 1 and 6 months after switching from TDF to TAF ( 44 ).…”
Section: Discussionmentioning
confidence: 76%
“…It is necessary to verify these findings in a bigger number of patients, and to examine long‐term therapeutic effects past 1 year. We previously reported that the therapeutic effects of TAF and TDF in naïve patients were comparable, and the HBsAg reduction by TAF and TDF was analyzed in the same group in this study. However, considering it has not sufficiently been verified whether the treatment effect of switching is equivalent, it is necessary to compare effects between TAF and TDF in a large cohort.…”
Section: Discussionmentioning
confidence: 65%
“…Recently, tenofovir alafenamide (TAF), which was designed to exhibit greater plasma stability compared with TDF, was approved for clinical application. TAF is as effective as TDF and leads to continuous improvement in renal and bone safety in the treatment of patients with chronic hepatitis B (CHB) 12 15 . Reports of the reduction of the risk of HCC development induced by TAF are scarce, because of their short observation periods.…”
Section: Introductionmentioning
confidence: 99%